Both Male and Female Malfunction Contributes to Yield Reduction under Water Stress during Meiosis in Bread Wheat - Onyemaobi, Ifeyinwa; Liu, Hui; Siddique, Kadambot H. M.; Yan, Guijun (Frontiers in Plant Science, 2017)
Water stress during meiosis in wheat is a major constraint to yield especially for the rainfed farming regions. Pollen sterility has been proposed as the most sensitive process leading to low seed set (low % of fertile spikelets), but here we show this is not universal, and that the development of female reproductive parts is equally if not more sensitive than male parts in many wheat cultivars. The first experiment examined water stress during meiosis in 46 wheat genotypes. The reduction in seed set varied widely, ranging from 6 to 48%. The second experiment differentiated the effect of water stress on the male or the female reproductive part in 13 wheat genotypes. Water stress was imposed during meiosis, with plants cross-pollinated 5 days later with pollen from stressed or unstressed plants used to pollinate emasculated stressed or unstressed female parts. Seed set and kernel weight were measured at maturity. Contrary to the well-held view that the male reproductive part is the major contributor to seed set reduction when water stress is experienced during meiosis, the stressed-female part was also a predominant contributor in four wheat genotypes among the 13 genotypes examined. This strongly indicates that both male and female parts are responsible for yield reduction when water-stressed during meiosis and suggests that it may be possible to breed tolerant wheat cultivars combining tolerance from both male and female reproductive parts.